Low power fundamental VCO design in D-band using 0.13 µm SiGe BiCMOS technology - Ali, U.; Fischer, G.; Thiede, Andreas (2015 German Microwave Conference)

Optimierung der monotonen und zyklischen Eigenschaften von hoch manganhaltigen TWIP-Stählen – Einfluss von Temperatur und Vorverformung auf die Mikrostrukturentwicklung - Rüsing, Christian Johannes

Multiple Loop Self-Triggered Model Predictive Control for Network Scheduling and Control - Henriksson, E.; Quevedo, D. E.; Peters, Edwin G. W.; Sandberg, H.; Johansson, K. H. (CDC)

Uniform Global Asymptotic Stability of Networked Control Systems Affected with Packet Dropouts and Scheduling Issues - Lješnjanin, M.; Nešić, D.; Quevedo, D. E.

Fake-Acknowledgment Attack on ACK-Based Sensor Power Schedule for Remote State Estimation - Li, Y.; Quevedo, D. E.; Dey, S.; Shi, L.

Co-design for Control and Scheduling over Wireless Industrial Control Networks - Peters, E. G. W.; Quevedo, D. E.; Fu, M.

Event-triggered Anytime Control with Two Controllers - Huang, K. Q.; Dang, T. V.; Ling, K. V.; Quevedo, D. E.

Jamming Attacks on Remote State Estimation in Cyber-Physical Systems: A Game-Theoretic Approach - Li, Y.; Shi, L.; Cheng, P.; Chen, J.; Quevedo, D. E. (TAC)

Distortion Minimization in Multi-Sensor Estimation Using Energy Harvesting and Energy Sharing - Knorn, S.; Dey, S.; Ahlén, A.; Quevedo, D. E. (TSP)

Data-driven power control for state estimation: A Bayesian inference approach - Wu, J.; Li, Y.; Quevedo, D. E.; Lau, V.; Shi, L. (AUTO)

Flachheitsbasierte Methode zum stoßfreien Umschalten von Reglerstrukturen - Osmic, Semir

Ein Beitrag zur Verarbeitung von Dickblech aus utlrahochfesten Stahlwerkstoffen - Rostek, Tim
Die Fertigung von innovativen Bauteilen aus ultrahochfesten Stählen erfordert oft Wärmebehandlungen zur Einstellung höchster mechanischer Festigkeiten. Bei Einsatz dickwandiger Halbzeuge mit entsprechend hoher Wärmekapazität eignen sich konventionelle Wärmebehandlungstechnologien und -prozessführungen jedoch nur eingeschränkt für einen effizienten Herstellungsprozess. Inhalt dieser Arbeit sind daher innovative Fertigungsstrategien, welche die wirtschaftliche Herstellung entsprechender Bauteile vor dem Hintergrund einer effektiven Formgebung sowie einer anforderungsangepassten Werkstoffbehandlung zum Ziel haben. Spezielle Temperaturführungsstrategien als auch thermomechanische Herangehensweisen zum Einstellen besonders günstiger mechanischer Eigenschaften entsprechender Stahlwerkstoffe stellen in diesem Kontext vielversprechende Ansatzpunkte dar.

Hans Werner Henze und seine Zeit - Tumat, Antje (Musiktheorie)

Monolithic on-chip integration of semiconductor waveguides, beamsplitters and single-photon sources - Jöns, Klaus D.; U. Rengstl, U; Ostermann, M; Hargart, F; Heldmaier, M; Bounouar, S; Ulrich, S.M; Jetter, M; Michler, P

Earenfight, Theresa: Queenship in Medieval Europe - Foerster, Anne (Das Mittelalter)

Einfluss von Werkstoff, Prozessführung und Wärmebehandlung auf das bruchmechanische Verhalten von Laserstrahlschmelzbauteilen - Riemer, Andre

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (International Colloquium on Automata, Languages, and Programming (ICALP 2015))
The study of ground state energies of local Hamiltonians has played a fundamental role in quantum complexity theory. In this paper, we take a new direction by introducing the physically motivated notion of ``ground state connectivity'' of local Hamiltonians, which captures problems in areas ranging from quantum stabilizer codes to quantum memories. We show that determining how ``connected'' the ground space of a local Hamiltonian is can range from QCMA-complete to PSPACE-complete, as well as NEXP-complete for an appropriately defined ``succinct'' version of the problem. As a result, we obtain a natural QCMA-complete problem, a goal which has generally proven difficult since the conception of QCMA over a decade ago. Our proofs rely on a new technical tool, the Traversal Lemma, which analyzes the Hilbert space a local unitary evolution must traverse under certain conditions. We show that this lemma is essentially tight with respect to the length of the unitary evolution in question.

Quantum Hamiltonian Complexity - Gharibian, Sevag; Huang, Yichen; Landau, Zeph; Woo Shin, Seung (Foundations and Trends® in Theoretical Computer Science)
Constraint satisfaction problems are a central pillar of modern computational complexity theory. This survey provides an introduction to the rapidly growing field of Quantum Hamiltonian Complexity, which includes the study of quantum constraint satisfaction problems. Over the past decade and a half, this field has witnessed fundamental breakthroughs, ranging from the establishment of a “Quantum Cook-Levin Theorem” to deep insights into the structure of 1D low-temperature quantum systems via so-called area laws. Our aim here is to provide a computer science-oriented introduction to the subject in order to help bridge the language barrier between computer scientists and physicists in the field. As such, we include the following in this survey: (1) The motivations and history of the field, (2) a glossary of condensed matter physics terms explained in computer-science friendly language, (3) overviews of central ideas from condensed matter physics, such as indistinguishable particles, mean field theory, tensor networks, and area laws, and (4) brief expositions of selected computer science-based results in the area. For example, as part of the latter, we provide a novel information theoretic presentation of Bravyi’s polynomial time algorithm for Quantum 2-SAT.

Tensor network non-zero testing - Gharibian, Sevag; Landau, Zeph; Woo Shin, Seung; Wang, Guoming (Quantum Information & Computation)
Tensor networks are a central tool in condensed matter physics. In this paper, we initiate the study of tensor network non-zero testing (TNZ): Given a tensor network T, does T represent a non-zero vector? We show that TNZ is not in the Polynomial-Time Hierarchy unless the hierarchy collapses. We next show (among other results) that the special cases of TNZ on non-negative and injective tensor networks are in NP. Using this, we make a simple observation: The commuting variant of the MA-complete stoquastic k-SAT problem on D-dimensional qudits is in NP for logarithmic k and constant D. This reveals the first class of quantum Hamiltonians whose commuting variant is known to be in NP for all (1) logarithmic k, (2) constant D, and (3) for arbitrary interaction graphs.

Entwicklung einer Kennwertprognose für mit Blindnietelementen elementar gefügte CFK- Mischbauverbindungen auf Basis von experimentellen Untersuchungen - Hessing , Florian

Charakterisierung des Trag- und Bruchverhaltens von Punktschweißverbindungen aus hochfesten Mangan-Bor-Stählen - Klokkers, Frederik

Auswirkungen von fügeprozessbedingten Delaminationen auf die mechanischen Eigenschaften von halbhohlstanzgenieteten Mischbauverbindungen aus Faserverbundkunststoffen und Aluminium - Plass, Michael

Materialcharakterisierung und -modellierung zur Simulation von Klebverbindungen mit Polyurethanklebstoffen - Sikora, Sebastian Patrick

Entwicklung und Qualifizierung eines Funktionselementes für das einseitige, vorlochfreie Fügen im Karosserierohbau - Westhoff, Dirk

Untersuchungen zur Prozesskette beim Kleben von CFK-Strukturbauteilen in Leichtbaukarosserien - Brodd, Alexander

Qualifizierung des vorlochfreien Direktverschraubens von CFK-Mischbaustrukturen für den Einsatz im Automobilbau - Somnitz, Andreas

Dijital Emek ve Karl Marx - Fuchs, Christian

Culture and Economy in the Age of Social Media - Fuchs, Christian

Reconsidering Value and Labour in the Digital Age

Zur Theoriebildung und Analyse der digitalen Arbeit. Die globale Produktion digitaler Hard- und Software (Teil I) - Fuchs, Christian (Z 103)

Internet, Kapitalismus und periphere Entwicklung im Waldviertel - Fuchs, Christian (Momentum Quarterly – Zeitschrift für sozialen Fortschritt (Journal for Societal Progress))

Internet, Capitalism, and Peripheral Development in the Waldviertel - Fuchs, Christian (New Proposals)

Towards a Theoretical Model of Social Media Surveillance in Contemporary Society - Fuchs, Christian; Trottier, Daniel (Communications: The European Journal of Communication Research)

The Macbride Report in Twenty-First-Century Capitalism, the Age of Social Media and the BRICS Countries - Fuchs, Christian (Javnost: The Public)

Power in the Age of Social Media - Fuchs, Christian (Heathwood Journal of Critical Theory)

Social Media Surveillance - Fuchs, Christian (Handbook of Digital Politics)

Martin-Heidegger’s anti-Semitism: Philosophy of Technology and the Media in the Light of the “Black Notebooks“. Implications for the Reception of Heidegger in Media and Communication Studies - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Left-Wing Media Politics and the Advertising Tax. Reflections on Astra Taylor’s Nook “The People’s Platform: Taking Back Power and Culture in the Digital Age“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Surveillance and Critical Theory. In Surveillance: Critical Analysis and Current Challenges: Special issue edited by James Schwoch, John Laprise and Ivory Mills - Fuchs, Christian (Media and Communication)

Digital Labour: A Comment on César Bolaño’s tripleC Reflection - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Antisemitismo e tecnofobia: il quarto volume dei Quaderni neri di Martin Heidegger (1942-1948) - Fuchs, Christian (Kasparhauser, September 15, 2015)

The Internet, Freedom, and Ideology in the Age of Mass Surveillance - Fuchs, Christian (The Opticon – A Newspaper on Privacy and Surveillance)

Against Divisiveness: Digital Workers of the World Unite! A Rejoinder to César Bolaño and Eloy Vieira - Fuchs, Christian (Television & New Media)

Why we need alternative social media before it is too late - Fuchs, Christian (Connect-World, Global-ICT 2014)

Updated Plan for Use and Foreground. Deliverable D5.3 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Fuchs, Christian; Bellanova, Rocco

Validation Report. Deliverable D5.3 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Fuchs, Christian

Flexible Electronics: Integration Processes for Organic and Inorganic Semiconductor-Based Thin-Film Transistors - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Electronics)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Hardware and Architecture; Signal Processing; Control and Systems Engineering

Silicon Nanoparticles contacted by metal nanogaps for FET applications - Wolff, K; Hilleringmann, Ulrich

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)
We present radiation mechanism exhibited by a higher order soliton. In a course of its evolution the higher-order soliton emits polychromatic radiation resulting in formation of multipeak frequency comb-like spectral band. The shape and spectral position of this band can be effectively controlled by the relative strength of the third order dispersion. An analytical description is corroborated by numerical simulations. It is shown that for longer pulses the described effect persists also under the action of higher order perturbations such as Raman and self-steepening.

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Yulin, A. V.; Driben, R. (Optics Letters)
The effect of mutual interactions between dark solitons and dispersive waves is investigated numerically and analytically. The condition of the resonant scattering of dispersive waves on dark solitons is derived and compared against the results of the numerical simulations. It is shown that the interaction with intense dispersive waves affects the dynamics of the solitons by accelerating, decelerating, or destroying them. It is also demonstrated that two dark solitons can form a cavity for dispersive waves bouncing between the two dark solitons. The differences of the resonant scattering of the dispersive waves on dark and bright solitons are discussed. In particular, we demonstrate that two dark solitons and a dispersive wave bouncing in between them create a solitonic cavity with convex “mirrors,” unlike the concave “mirror” in the case of bright solitons.

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Die Manipulation der Bedürfnisse. Zum Verhältnis von Kritik und Geist der Werbung - Hälterlein, Jens (Sociologia Internationalis. Europäische Zeitschrift für Kulturforschung)

Die Regierung des Konsums - Hälterlein, Jens

Vectorial self-accelerating beams - Meier, Torsten; Driben, R.; Konotop, V.V. (European Conference on Lasers and Electro-Optics - European Quantum Electronics Conference)
The discovery of Airy waves, in the context of solutions to the linear Schrödinger equation [1], inspired extensive research for self-accelerating waves in optical settings [2-6]. Fascinating self-accelerating, self-healing light beams propagating along the bending trajectories can manifest themself in the spatial and the temporal domains and are promising for a large variety of potential applications.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Non-coaxial vortices in two-component Bose-Einstein condensates: Persistent precession and nutation - Meier, Torsten; Driben, R.; Konotop, V.V. (arXiv preprint arXiv:1505.04113)
It is demonstrated that a two-component Bose-Einstein condensate (BEC) with all-repulsive inter-atomic interactions loaded into a radially symmetric harmonic trap supports robust non-coaxial vortices with approximately orthogonal vortex lines in each of the components. These cross vortices are excited from the linear modes by a sudden switch-on of the nonlinearity (via Feshbach resonance) and are characterized by persistent dynamical regimes of precession with nutation, resembling the motion of a rigid body. The obtained dynamics can be understood qualitatively on the basis of a simple mechanical model.

Psalmen ohne Worte. Ein instrumentales Zwischenspiel aus den letzten zwei Jahrhunderten - Schroeter-Wittke, Harald (Theologie des Psalters. Günter Bader zum 70. Geburtstag)

Zukunft als Verfall? Transformationsprospekte von Kirche angesichts der Transformationen von Gesellschaft - Schroeter-Wittke, Harald (Praktische Theologie)

Aalaiki'ssalaam. Zum 60. Geburtstag von Naji Hakim - Schroeter-Wittke, Harald (Praktische Theologie)

Moderation - Schroeter-Wittke, Harald (Qualität im Gottesdienst)

Hirnbissige Massenveranstaltung - Schroeter-Wittke, Harald (Paderborner Universitätszeitung Wintersemester 15/16)

Pädagogik im Zeitalter der Reformation – eine Sammelrezension: Bernd Schröder (Hg.): Johannes Sturm (1507-1589). Pädagoge der Reformation, Jena 2009 – Mathieu Arnold (Hg.): Johannes Sturm (1507-1589). Rhetor, Pädagoge und Diplomat, Tübingen 2009 – Gerlinde Huber-Rebenich (Hg.): Lehren und Lernen im Zeitalter der Reformation, Tübingen 2012 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Sebastian Berndt: Gott haßt die Jünger der Lüge. Ein Versuch über Metal und Christentum: Metal als gesellschaftliches Zeitphänomen mit ethischen und religiösen Implikationen. Hamburg 2012 - Schroeter-Wittke, Harald (Theologische Literaturzeitung)

Mirjam Zimmermann / Ruben Zimmermann (Hg.): Handbuch Bibeldidaktik, Tübingen 2013 - Schroeter-Wittke, Harald (Theologische Literaturzeitung)

Buß- und Bettag (18.11.2015). Lk 13,(1-5)6-9: Denkt um! - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

1. Sam. 16,14-23. Kantate. Predigtstudie zum Sonntag Kantate: Wie man gut wird (Reihe I) - Schroeter-Wittke, Harald; Kirsner, Inge (www.stichwortp.de, 03.05.2015)

18. Sonntag nach Trinitatis. Markus 12,28-34: Wenn zwei sich nahekommen - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien I/2)

Trabajadores Digitales del mundo, uníos! Un marco para teorizar críticamente y analizar el trabajo digital - Fuchs, Christian; Sandoval, Marisol (Revista Hipertextos: Capitalismo, Técnica y Sociedad en debate)

Trabalhadores digitais do mundo inteiro uni-vos: teorizando e analisando criticamente o trabalho digital - Fuchs, Christian; Sandoval, Marisol (Parágrafo: Revista Científica de Comunicação Social da FIAM-FAAM)

Zur Theoriebildung und Analyse der digitalen Arbeit. Die globale Produktion digitaler Hard- und Software (Teil II) - Fuchs, Christian (Z 104)

The Digital Labour Theory of Value in the Age of Facebook, YouTube, Twitter and Weibo - Fuchs, Christian (Reconsidering Value and Labour in the Digital Age)

SThe Political Economy of Capitalist and Alternative Social Media - Fuchs, Christian; Sandoval, Marisol (The Routledge Companion to Alternative and Community Media)

Introduction: Value and Labour in the Digital Age - Fuchs, Christian; Fisher, Eran (Reconsidering Value and Labour in the Digital Age)

Dallas Smythe and Digital Labor - Fuchs, Christian (Routledge Companion to Labor and Media)

The Internet, Social Media and Axel Honneth’s Interpretation of Georg Lukács’ Theory of Reification andAalienation - Fuchs, Christian (Westminster Advanced Studies Research Paper)

Christian Fuchs (Interview conducted by Michelle Amazeen) - Fuchs, Christian (Key Thinkers in Critical Communication Scholarship: From the Pioneers to the Next Generation)

Mídias Sociais e a Esfera Pública - Fuchs, Christian (Revista Contracampo)

Anti-Semitism, Anti-Marxism, and Technophobia: The Fourth Volume of Martin Heidegger’s Black Notebooks (1942-1948) - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Reflections on Todd Wolfson’s Book “Digital Rebellion: The Birth of the Cyber Left” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Krise, Kommunikation, Kapitalismus. Zur Kritik der politischen Ökonomie sozialer Medien - Fuchs, Christian (Luxemburg 1/2015)

Tecnica, antisemitismo e media. I Quaderni neri di Martin Heidegger - Fuchs, Christian (Kasparhauser 12 (2015))

Surface-modified CAU-10 MOF materials as humidity sensors: impedance spectroscopic study on water uptake - Weiss, Alexander; Reimer, Nele; Stock, Norbert; Tiemann, Michael; Wagner, Thorsten (Physical Chemistry Chemical Physics)
Metal–organic frameworks (MOFs) are crystalline microporous materials with tunable chemical and physical properties. By combining various metal clusters with different interconnecting organic linkers, the pore structure, crystallinity, as well as the surface properties can be modified. In the present work, modification of the organic linker molecules is utilized to synthesize CAU-10 type MOFs with variable affinity of the pore surface to water. In principle, this should influence the accessibility of the pores for water vapor and therefore offer a tool to control its sorption properties. For a deeper understanding we studied the water sorption characteristics and compared the results to the conductive and dielectric properties studied by impedance spectroscopy. Spectra in a wide frequency range from 1 mHz to 1 MHz were recorded. Data analysis is performed using the Havriliak–Negami model. The MOFs are also tested as sensitive layers for capacitive humidity sensing by correlating the change in permittivity of the materials with the amount of physisorbed water. Such an MOF-based sensor was tested with respect to environmental monitoring and compared to a commonly used commercial humidity sensor.

Synthesis of Mesoporous Metal Oxides by Structure Replication: Thermal Analysis of Metal Nitrates in Porous Carbon Matrices - Weinberger, Christian; Roggenbuck, Jan; Hanss, Jan; Tiemann, Michael (Nanomaterials)
A variety of metal nitrates were filled into the pores of an ordered mesoporous CMK-3 carbon matrix by solution-based impregnation. Thermal conversion of the metal nitrates into the respective metal oxides, and subsequent removal of the carbon matrix by thermal combustion, provides a versatile means to prepare mesoporous metal oxides (so-called nanocasting). This study aims to monitor the thermally induced processes by thermogravimetric analysis (TGA), coupled with mass ion detection (MS). The highly dispersed metal nitrates in the pores of the carbon matrix tend to react to the respective metal oxides at lower temperature than reported in the literature for pure, i.e., carbon-free, metal nitrates. The subsequent thermal combustion of the CMK-3 carbon matrix also occurs at lower temperature, which is explained by a catalytic effect of the metal oxides present in the pores. This catalytic effect is particularly strong for oxides of redox active metals, such as transition group VII and VIII metals (Mn, Fe, Co, Ni), Cu, and Ce.

Light-activated resistive ozone sensing at room temperature utilizing nanoporous In2O3 particles: Influence of particle size - Klaus, Dominik; Klawinski, Danielle; Amrehn, Sabrina; Tiemann, Michael; Wagner, Thorsten (Sensors and Actuators B: Chemical)
Ordered mesoporous In2O3 particles of variable size synthesized by the nanocasting method are used for preparation of resistive gas-sensing layers. Light activation by a LED (blue light, 460 nm) permits room-temperature ozone sensing. Apart from differences in base-line resistance in sensing layers containing small (diameter approx. 170 nm) or large particles (approx. 870 nm), differences in the response amplitude and response time constant are also observed. Signal stabilization is achieved faster for small particles. In addition, sensors show a particle size-dependent reaction threshold for low ozone concentration. Larger particles show negligible response to 50 ppb ozone whereas a significant response is observed for the small-particle sensors. A simple model based on geometrical properties and formation of depletion layers explaining the observed behavior is presented.

Nanostructured Co3O4 as a CO gas sensor: Temperature-dependent behavior - Vetter, S.; Haffer, S.; Wagner, T.; Tiemann, Michael (Sensors and Actuators B: Chemical)
Cobalt oxide spinel (Co3O4) with an ordered nanostructure is used as a resistive gas sensor for carbon monoxide (CO) in low ppm concentrations. The operating temperature has a strong impact on the concentration-dependent sensing behavior. At lower temperature (473 K) the sensor response is governed mainly by surface coverage with CO and/or CO2, whereas at higher temperature (563 K) oxygen diffusion in the crystal lattice of Co3O4 strongly affects the sensing behavior.

Textile Erinnerung - Kraft, Kerstin

Privatsphäre als Privileg: Der US-Rechtswissenschaftler Frank Pasquale ist dem Klassenwiderspruch in der digitalen Gesellschaft auf der Spur - Allmer, Thomas (junge Welt)

Critical Theory and Social Media: Between Emancipation and Commodification - Allmer, Thomas

Das Versteckte Internet - Karaboga, Murat; Matzner, Tobias; Morlok, Tina; Pittroff, Fabian; Nebel, Maxi; Ochs, Carsten; von Pape, Thilo; Pörschke, Julia Victoria; Schütz, Philip; Simo Fhom, Hervais (Whitepaper des Forums Privatheit und Selbstbestimmung in der digitalen Welt)

How Smart Is “Smart Security”? Exploring Data Subjectivity and Resistance. Final Report - Baur-Ahrens, Andreas; Krüger, Marco; Ammicht Quinn, Regina; Leese, Matthias; Matzner, Tobias

Politische Öffentlichkeit und Big Data - Matzner, Tobias; Heesen, Jessica (Privatheit, Öffentlichkeit und demokratische Willensbildung in Zeiten von Big Data)

Sicherheitsethik in der Anwendung: Ein Praxistest gesellschaftlicher Begleitforschung - Matzner, Tobias; Ammicht Quinn, Regina (Sichere Zeiten?)

Ethik ohne Garantien - Matzner, Tobias (Ethik in den Wissenschaften)

Nanometer Scale Electronic Device Integration Using Side-Wall Deposition and Etch-Back Technology - Hilleringmann, Ulrich; Assion, F.; Vidor, F. F.; Wirth, G. I. (Journal of Machine to Machine Communications)
Keywords: General Medicine

Application of side-wall deposition and etch-back technology for nanometer scale device integration - Hilleringmann, Ulrich; Vidor, F.F.; Assion, F. (Proceedings of the 2nd Pan African International Conference on Science, Computing and Telecommunications (PACT 2014))

Extended event-driven modeling of a ΣΔ-fractional-N PLL including non-ideal effects - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2014 21st IEEE International Conference on Electronics, Circuits and Systems (ICECS))

Fast and accurate event-driven simulation of a mixed-signal system using the example of a PLL - Hangmann, C; Hedayat, C; Hilleringmann, Ulrich (Proc. Int. Conf. Exhib. Integr. Issues Miniatured Syst.)

Religion und Krieg im Medium der Musik: Deutsche Oratorien im Ersten Weltkrieg - Höink, Dominik (Louis Spohr Symposium Braunschweig 2014: „Musik und Politik“. Politische Einflüsse auf Musikerbiografien und kompositorisches Schaffen von 1784 bis heute)

Louis Spohrs Der Fall Babylons und die ,Belsazardramen‘ seit Georg Friedrich Händel - Höink, Dominik (Die Oratorien Louis Spohrs. Kontext – Text – Musik)